Nilai Moralitas Sabha Parwa dalam Viracarita Mahabharata - Yunita Dwi Astutik; Toto Margiyono; Shinta Tyas Pratisthita (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2026)
This study explores the moral values contained in the Sabha Parwa section of Kamala Subramaniam's Vīracaritaṁ Mahābhārata. As a literary work based on Hindu Itihasa, Sabha Parwa depicts the moral decay and abuse of power within the royal court, particularly through the manipulated dice game that led to the downfall of the Pandavas and the humiliation of Draupadi. The primary issue addressed is how moral values in this classical text can be interpreted contextually to address the multidimensional moral degradation in contemporary society, such as corruption, violence, and the erosion of integrity. This qualitative research employs Gadamer's hermeneutic approach to interpret moral meanings behind dialogues and events in the text, bridging the values of ancient literature with modern understanding. The primary data source is Kamala Subramaniam's Mahabharata (2007), supplemented by secondary sources including books, journals, and related articles. Data collection was carried out through literature study and non-participant text observation. The analysis identifies six main moral values: justice and truth (dharma), responsibility and integrity, loyalty and betrayal, women's honor and dignity, self-control and the danger of desire, and religiosity and steadfastness. These values are highly relevant for strengthening character education and building ethical awareness in the digital era. The findings confirm that Sabha Parwa is not merely an ancient epic but a relevant moral reflection for addressing various forms of injustice and moral deviation in modern life.